Combined immunodeficiency caused by pathogenic variants in the ZAP70 C-terminal SH2 domain - Mongellaz, Cédric; Vicente, Rita; Noroski, Lenora M.; Noraz, Nelly; Courgnaud, Valérie; Chinen, Javier; Faria, Emilia; Zimmermann, Valérie S.; Taylor, Naomi (Frontiers in Immunology, 2023)
ZAP-70, a protein tyrosine kinase recruited to the T cell receptor (TCR), initiates a TCR signaling cascade upon antigen stimulation. Mutations in the ZAP70 gene cause a combined immunodeficiency characterized by low or absent CD8+ T cells and nonfunctional CD4+ T cells. Most deleterious missense ZAP70 mutations in patients are located in the kinase domain but the impact of mutations in the SH2 domains, regulating ZAP-70 recruitment to the TCR, are not well understood. Genetic analyses of an infant who presented with pneumocystis pneumonia, mycobacterial infection, and an absence of CD8 T cells revealed a novel homozygous mutation in the C-terminal SH2 domain (SH2-C) of the ZAP70 gene (c.C343T, p.R170C). A distantly related second patient was found to be compound heterozygous for the R170C variant and a 13bp deletion in the ZAP70 kinase domain. While the R170C mutant was highly expressed, there was an absence of TCR-induced proliferation, associated with significantly attenuated TCR-induced ZAP-70 phosphorylation and a lack of binding of ZAP-70 to TCR-ζ. Moreover, a homozygous ZAP-70 R192W variant was identified in 2 siblings with combined immunodeficiency and CD8 lymphopenia, confirming the pathogenicity of this mutation. Structural modeling of this region revealed the critical nature of the arginines at positions 170 and 192, in concert with R190, forming a binding pocket for the phosphorylated TCR-ζ chain. Thus, deleterious mutations in the SH2-C domain result in attenuated ZAP-70 function and clinical manifestations of immunodeficiency.